A Comprehensive Review on The Activities Of 5th Generation Mobile Communication System - Vishakha Tomar, (AG Volumes, 2022)
5G is the fifth generation of mobile networks. A new wireless standard has emerged in the wake of 1G, 2G, 3G, & 4G networks throughout the world. It is possible to create a new form of the network which is meant to link almost everyone & everything together, including objects, machines as well as devices. This next generation of wireless technology, dubbed "5G," is designed to provide consumers with faster download and upload speeds up to 10 Gbps (gigabits per second), ultra-low latency, enhanced dependability, vast network capacity, and a more consistent user experience. New user experiences, as well as new industries, are enabled by enhanced performance as well as efficiency. In addition, it is anticipated that the 5G IoT (Internet of Things) ecosystem would unleash a massive 5G IoT ecosystem in which the networks will be able to satisfy the communication needs of billions of connected devices with the appropriate trade-offs between the speed, latency, as well as cost.